Finite Element Simulation of a SAW Motor based on Dual Friction-Drive. (2017) - Behera, Basudeba; Nemade, Harshal B.
Abstract: The paper presents a finite element simulation and analysis of a dual friction-drive surface acoustic wave (SAW) motor. The SAW motor consists of a cylindrical slider placed between two identical lithium niobate (LiNbO3 or LN) stators facing each other. Typically the LN stator contains an interdigital transducer (IDT) fabricated on either side of it so that the application of sinusoidal voltage excitation to the IDT generates travelling Rayleigh SAW on the surface of the stator. The SAWs propagating in the two stators interact with the slider and under the preload applied on the stators the generated frictional force drives the slider. The direction of motion of the slider can be reversed by reversing the direction of SAWs. Finite element simulation of the motor is carried out to study the characteristics such as displacement and velocity of the slider for sinusoidal excitation.